Pedro Juan Núñez y la enseñanza de Hermógenes - Grau Codina, Ferran (Euphrosyne: Revista de filología clássica, 2002)
In this article Pedro Juan Núñez´ ideas on rhetoric and its actual teaching at the University are examined. An evolution from the influence of Ramist rhetoric to the Hellenistic rhetoric of Hermogenes can be seen, but this evolution is consistent with Núñez`ideas on “method of teaching” in his long life as a scholar. We try to explain the practical teaching of Núñez through manuscripts on rhetoric, the combination in practice of materials from different traditions, and the adaptation of these materials to the teaching of rhetoric.